Adolescents and reproductive health: Promoting healthy habits for reproductive well-being - Sri Sumaryani; Heni Purwaningsih (Universitas Muhammadiyah Malang, 2024)
Adolescence is characterized by rapid physical, psychological, cognitive, emotional, and reproductive changes. Providing accurate and sufficient information is crucial in preparing young individuals to face these changes. This program aims to improve the understanding of reproductive health, namely puberty, among early adolescents in grades IV and V (aged 10-14 years) at Banyuurip Elementary School. The design utilized is a quasi-experimental method including pre-test and post-test assessments. Thirty-eight students were chosen for this study by purposive sampling. The program's effectiveness is evaluated by a questionnaire, and the data is analyzed using a paired t-test. The data shows a notable difference in knowledge levels before and after obtaining health education through lectures and chats. Prior to health education implementation, most students demonstrated low knowledge levels (52.6%), followed by moderate levels (42.3%), while a tiny proportion had high knowledge levels (5.1%). After health education interventions, students' knowledge levels showed considerable improvement: 29% high, 71% sufficient, and 0% low. The average score increased from 76.58 before therapy to 83.16 after treatment. The median values were 80 and 90. The paired t-test yielded a p-value of 0.049, suggesting that reproductive health education significantly improved students' knowledge at Banyuurip Elementary School. The study indicates that health education could improve students' understanding of puberty and the maintenance of reproductive health.